2014
DOI: 10.7162/s1809-97772013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surgery in the treatment of crista galli pneumatization evolving with localizated frontal headaches

Abstract: Summary Introduction: The crista galli is part of the ethmoid bone and thus may suffer from the process of pneumatization. Pneumatization occurs in between 3% and 14% of patients, resulting from air cells in the frontal or ethmoid sinuses. Aim: To describe 3 cases of crista galli pneumatization in which the patients developed infection and were treated surgically by endoscopic techniques. Method: We present 3 case studies of patients complaining of severe frontal headaches. The patients underwent ENT evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, a different study assessed the origin of the CG pneumatization as either frontal, or ethmoidal [12]. The incidence of such air space of the CG was evaluated in different studies (Table 1) and it seemingly depends on the population which is studied [13]. Before Mladina et al study [1], Lei et al performed a study in 32 patients to investigate the occurrence rate of pneumatization of the PPE and found the PPE pneumatization in six cases, thus in 18.75% [23].…”
Section:  Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a different study assessed the origin of the CG pneumatization as either frontal, or ethmoidal [12]. The incidence of such air space of the CG was evaluated in different studies (Table 1) and it seemingly depends on the population which is studied [13]. Before Mladina et al study [1], Lei et al performed a study in 32 patients to investigate the occurrence rate of pneumatization of the PPE and found the PPE pneumatization in six cases, thus in 18.75% [23].…”
Section:  Discussionmentioning
confidence: 99%
“…Nevertheless, a different study assessed the origin of the CG pneumatization as either frontal, or ethmoidal [ 12 ]. The incidence of such air space of the CG was evaluated in different studies (Table 1 ) and it seemingly depends on the population which is studied [ 13 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…In case of ostial blockage, an inflammatory -infectious response, similar to a regular rhinosinusitis, can occur. Socher et al 7 reported 3 clinical cases in which chronic headache were attributed to the inflammatory process within the pneumatized crista galli. They succeeded to endoscopically remove the inflammatory changed mucosa within the pneumatized crista galli and the outcomes in all three patients have been excellent!…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of pneumatized crista galli varies a lot according to different authors, from 3-37.5% [3][4][5][6] . There are several theories explaining the pneumatization of crista galli, but the most widely accepted are two: the first that advocates pneumatization from the ethmoid sinus and another one that advocates crista galli pneumatization from the frontal sinus 7 . The communication between the pneumatized crista galli and the adjacent paranasal structures usually happens through an opening similar to other sinus ostia, opened in most of the cases in the frontal sinus cavity 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation